AKUNTANSI SYARIAH PADA PEMBIAYAAN PEMILIKAN RUMAH (PPR) DENGAN AKAD MURABAHAH - Tsarina Zenabia; Fina Fitriyana; Yolanda Gusvia Putri; Anum Nuryani; Tati Rosyati (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of the implementation of Community Service entitled "Sharia Accounting for Financing Home Ownership with a Murabahah Contracts" is a form of fulfilling the obligations of the Higher Education Tri Dharma namely Community Service performed at the Citizen Hall of Pamulang Elok Housing RW 014, Depok on November 2, 2019 until by 3 November 2019. Based on the foregoing, community service activities by providing knowledge about home ownership financing at an Islamic bank using a murabahah contract, training and calculation of the installment ratio of PPR in recording Islamic accounting for the home financing transaction. The method used in this community service is in the form of counseling and training on understanding of murabaha accounting, differences in the calculation of Conventional Banks in using interest / Islamic Banks using Sharia ratios and providing knowledge of the dualism of the banking system in Indonesia, namely, Conventional Banks and Sharia Banks. The results of community service obtained are an understanding and desire of the PKM object to propose or move the financing of the ownership of they house at a Sharia Bank.Keywords: Sharia Banks, Sharia Accounting, Aqad Murabahah, Interest, Riba